Contextual Service as an Expression of Missioner Value in the Church of the Nazarene - Sapto Sunariyanti; Yupiter Hulu; Sukirdi; Seri Damarwanti; Natalia Mega Saputri (Sekolah Tinggi Theologia Nazarene Indonesia, 2022)
Worship is one of expression channel of human relationship with God through contextual worship, but the contextualization of worship also has the potenstial to lead to separation and devision of the Church. Shifting values in society also play a role so that worship has potential to experience a shift in values that are far different from its original essence, where worship can’t carry mission’s messages and foster missionary character in the congregation. This issue is interesting to study and leads to the need for the church to rebuild a correct theological basis in contextual worship. How to rebuild the theological basis of contextualized worship so that it fulfills the characteristics of missionary worship? These are question that will be answered in the study. The purpose of this research is to rebuild the theological basis of contextual worship to build the missionary character of the congregation. Worship in the Church of the Nazarene is carried out as an expression of the highest love for God which is full of missionary values. This research method will use a descriptive phenomenological analysis approach based on a literature review to explore the theological basis and get a bridge to the missionary Christian character. A study of culture is needed to get the sharpness of the contextualization aspect in worship, equipped with field observations to see its application in the field. It was concluded that it was necessary to return to teaching about building the theological and missionary foundations on contextuak worship to all practitioners and decision makers involved in contextual worship in the church through various teaching, monitoring and evaluation programs to all related parties.